2019
DOI: 10.1016/j.meatsci.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lamb body composition using in vivo bioimpedance analysis

Abstract: The objective of this study was to evaluate the potential of in vivo bioimpedance analysis (BIA) as a method to estimate body composition in lambs. Thirty-one Texel x Ile de France crossbreed ram lambs were slaughtered at pre-determined intervals of average weights of 20, 26, 32, and 38 kg. Before the slaughter of the animals, their body weight (BW) and body length (BL) were measured. The values for resistance (Rs) and reactance (Xc) were collected using a single-frequency BIA equipment (Model RJL Quantum II B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…BMI was calculated by dividing body weight by height squared (kg/m 2 ). Fat mass index (FMI) and VFA were measured by bioelectrical impedance analysis (BIA) using an Inbody 770 (BioSpace, Seoul, Korea), which was a convenient method for the measurement of body composition [ 23 ]. Triceps skinfold (TSF) and mid-arm circumference (MAC) were taken midway between the olecranon and acromion in the dominant hand with the arm hanging relaxed at the side.…”
Section: Methodsmentioning
confidence: 99%
“…BMI was calculated by dividing body weight by height squared (kg/m 2 ). Fat mass index (FMI) and VFA were measured by bioelectrical impedance analysis (BIA) using an Inbody 770 (BioSpace, Seoul, Korea), which was a convenient method for the measurement of body composition [ 23 ]. Triceps skinfold (TSF) and mid-arm circumference (MAC) were taken midway between the olecranon and acromion in the dominant hand with the arm hanging relaxed at the side.…”
Section: Methodsmentioning
confidence: 99%
“…Needles were placed dorsally ~1 cm off the midline. Measurements were recorded in 5-s intervals for 30 s, resulting in six total measurements that were averaged and used in estimation equations for live animals and hot carcasses in Table 1 (Berg and Marchello, 1994; Slanger et al, 1994; Moro et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, PA has been widely used as an indicator of the nutritional condition in human beings as well as in animal carcasses, of quality assessment and raw cow milk adulteration (1,2,9) .…”
Section: Phase Anglementioning
confidence: 99%
“…Some researchers (9) reported that they obtained weak relationship amongst most of the components of the carcasses. Moro et al (1) added phase angle, bioelectric volume, resistive and reactive density to their equations to associate with the components of the carcass since the resistive density can be related to these components and the reactive density might indicate the association with the concentration of lean mass.…”
Section: Bia For Body Composition and Carcasses Evaluation Of Farm Animalsmentioning
confidence: 99%
See 1 more Smart Citation